0514 A Pilot Hospital Intervention Program for Treatment of Obstructive Sleep Apnea. (12th April 2019) - Cheng, Shan; Beauchamp, William; Calero, Karel; Nallu, Sagarika; Cabral, Laiheng; Holderman, Deborah; Schoonover, Doris; Johnson, Linda; Anderson, W Mcdowell
Abstract: Introduction: Prevalence of obstructive sleep apnea (OSA) in the United States is greater than 6%, and may be as high as 25% or more in the elderly. The condition is associated with development of high blood pressure, pulmonary hypertension, heart attack, stroke, atrial fibrillation, motor vehicle accidents associated with the sleepiness, and death. These comorbidities may lead to hospital admission for other reasons. Much of the therapy has been directed towards outpatient treatment with continuous positive airway pressure (CPAP). Unfortunately, patient adherence to CPAP therapy is not optimal. We tested the hypothesis that an AASM Accredited Center, technologist driven protocol, can improve CPAP adherence in hospitalized patients. Methods: Tampa General Sleep Center (TGSC) staff noted that many in-patients were not compliant with CPAP and developed a quality improvement protocol that would address common issues preventing patients from using their machines. A consult process was developed in the TGSC EMR. Hospitalized patients who were non-compliant with CPAP received a Sleep Center consult and a technologist visited the patient to provide education and interventions for these issues. The average intervention took 30 minutes. The key components included: 1. Education on the cause of OSA and the need to treat based on comorbidities above, 2. Choosing a patient preferred mask, 3. Mask desensitization while awake. Results: In the current pilot program, 484 consults were placed to the Sleep Center from January to December 2017. Of the 484 patients, 450 patients or 93% agreed to use their CPAP after the intervention was completed. The most common reasons given for prior non-adherence were lack of education ("no one ever told me that"), poor fitting mask interface, and claustrophobia. Conclusion: Early results demonstrate that a sleep center technologist driven protocol can improve CPAP adherence in non-compliant patients. More study will be needed to monitor outcomes for this in-hospital intervention program, to document cost-effectiveness. Support (If Any)